Formation of Patterns in Granular Materials - Rehberg, Ingo; Scherer, Michael A.; Schröter, Matthias; Betat, André; Dury, Christian M.; Ristow, Gerald H.; Straßburger, Gunther (Evolution of Spontaneous Structures in Dissipative Continuous Systems, 1998)
In order to study the behaviour of fluidized granular material experimentally and numerically, we propose to investigate pattern-forming processes, because they can be easily observed and quantitatively characterized. We report measurements on five such systems, namely pattern formation of granular material i) by segregation, under the influence of ii) linear horizontal and iii) circular horizontal vibration, iv) water shear flow, and in v) a sedimenting suspension